Tackling Youth Unemployment: Evidence From a Labor Market Experiment in Uganda. Issue 6 (20th November 2020) - Alfonsi, Livia; Bandiera, Oriana; Bassi, Vittorio; Burgess, Robin; Rasul, Imran; Sulaiman, Munshi; Vitali, Anna
Abstract : We design a labor market experiment to compare demand‐ and supply‐side policies to tackle youth unemployment, a key issue in low‐income countries. The experiment tracks 1700 workers and 1500 firms over four years to compare the effect of offering workers either vocational training (VT) or firm‐provided training (FT) for six months in a common setting where youth unemployment is above 60%. Relative to control workers, we find that, averaged over three post‐intervention years, FT and VT workers: (i) enjoy large and similar upticks in sector‐specific skills, (ii) significantly improve their employment rates, and (iii) experience marked improvements in an index of labor market outcomes. These averages, however, mask differences in dynamics: FT gains materialize quickly but fade over time, while VT gains emerge slowly but are long‐lasting, leading VT worker employment and earning profiles to rise above those of FT workers. Estimating a job ladder model of worker search reveals the key reason for this: VT workers receive significantly higher rates of job offers when unemployed, thus hastening their movement back into work. This likely stems from the fact that the skills of VT workers are certified and therefore can be demonstrated to potential employers. Tackling youth unemployment by skilling youth using vocational training pre‐labor market entry therefore appears to be more effective than incentivizing firms through wage subsidies to hire and train young labor market entrants.